(3GdehGbas - (3eMeO Hf YHO GdLHGQ Hf GdMSf GdfaQjs
(3ChdgG (B:s
(3ehba GdYR Chbafj hbGd dj dG jSJbd Hg Ohfj TF hdGjUdM ef oOhfj HTF s
(3BNQgG (B:s
(3heG CfJ efj Jba aj QMeJj hJQLh YXje aVdj heZaQJj s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1891s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs